An Analysis of the Poem “Prison” by Krishna Sen ‘Ichchhuk’ Translated by Govinda Raj Bhattarai - Adhikari, Anup (Nepal Journal of Multidisciplinary Research, 2021)
Poetry is a form of art; to express emotions and feelings by the use of distinctive style, meaning, sound and rhythm. The poem presents the rebellious nature of the revolutionists to defeat the arbitrary through literature and is much privileged towards independence. The poet imagines such an awful condition that happens in the insurgency period and he is not able to equivalent the freedom of choice and action. Oligarchy creates fascism, besides it, the poet has used the literary term, ‘my friend’ in each stanza to denote all victimized citizens and inmates who are anguished from despotism. To uplift from authoritarianism regime and to live with full sovereignty the communist movement had played an appreciable role in the context of Nepal. The literary genre which is characterized by literature and cultural form of early modern England that is written while the author is confined in a location against his wills, such as a prison, jail, or house arrest is known as prison literature. Thus, the message or underlying meaning of the poem is such that the poet alerts the emperor and leaders to adopt a democratic model.